2018
DOI: 10.1002/mbo3.597
|View full text |Cite
|
Sign up to set email alerts
|

Responses of fungal community composition to long‐term chemical and organic fertilization strategies in Chinese Mollisols

Abstract: How fungi respond to long‐term fertilization in Chinese Mollisols as sensitive indicators of soil fertility has received limited attention. To broaden our knowledge, we used high‐throughput pyrosequencing and quantitative PCR to explore the response of soil fungal community to long‐term chemical and organic fertilization strategies. Soils were collected in a 35‐year field experiment with four treatments: no fertilizer, chemical phosphorus, and potassium fertilizer (PK), chemical phosphorus, potassium, and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…4F). Some species of the fungal genus Cyphellophora are potential pathogens (Decock et al, 2003; Ma et al, 2018), and the relative abundance of OTU1311 was correlated significantly with some soil properties, such as soil TC, TN, TP and AP (Table S7), suggesting that continuous cropping may promote the proliferation of pathogens (Guo et al, 2011; Ranzi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…4F). Some species of the fungal genus Cyphellophora are potential pathogens (Decock et al, 2003; Ma et al, 2018), and the relative abundance of OTU1311 was correlated significantly with some soil properties, such as soil TC, TN, TP and AP (Table S7), suggesting that continuous cropping may promote the proliferation of pathogens (Guo et al, 2011; Ranzi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also confirmed that NPS treatment had a higher relative abundance of Proteobacteria than other treatments, while the application of K fertilizer had no significant impact on the dominant bacterial groups (Figure 2). Both long-term and short-term studies have found that the abundance of Acidobacteria decreased significantly with the increase in NPK fertilizer, which was closely associated with soil pH value [56,60], whereas, in our study, the relative abundance of Acidobacteria, serving as typically oligotrophic bacteria in NP (15.4%) and NPKS (24.3%) treatments, was higher than that in NPK (13.6%) and NPS (14.8%) treatments, in contradiction with previous research. This may be related to the increase in the special subgroup function of Acidobacteria, which, in terms of the genus, were unclassified Subgroup 3, unclassified Subgroup 6, unclassified Subgroup 17, and uncultured Desulfovirga sp.…”
Section: Effects Of Long-term Straw Returning and K Fertilizer On The Soil Microbial Communitymentioning
confidence: 99%
“…We cannot find any documentation of Chaetomidium arxii infection in humans, although this genus is well known for its opportunistic animal and human pathogens ( 111 ).…”
Section: Supplementary Resultsmentioning
confidence: 90%